Strategi Komunikasi Medical Representative PT. Sanbe Farma dalam Upaya Menjaga Loyalitas Klien - Felicia Thaimiyah Putri; Agustrijanto (UNIVERSITAS KALBIS, 2022)
PT Sanbe Farma is one of the biggest pharmacy industry in Indonesia that grow with a lot of customer. PT Sanbe Farma’s Medical Representative is applied some interpersonal communication strategic to the client in purpose to maintain the client’s loyalities to the company. In analyzing towards how PT Sanbe Farma’s Medical Representative maintaining the loyalities of its clients, the researcher is using Interpersonali Communication Strategy theory as the main theory of this research.Yhis research is a study case research, with a qualitative approach through a in depth interview and the result is validated with triangulation technique and the paradigm is post positivistic. From this research, the readers can earn some information about the effectivity of the application of an Interpersonal Communication Strategy Theory by the Medical Representive, related to how its influence the loyalities and the number of product selling that makes PT Sanbe Farma is one of the biggest pharmacy industry in Indonesia.